Elevated Temperatures Impact on the Mechanical Behavior of Reactive Powder Concrete Containing Hybrid Fibers - Abdul Rasoul, Zainab M. R.; Mushtaq Sadiq Radh; Mahmmod, Laith Mohammed Ridha; Alsaad, Aymen J. (Journal of Pure & Applied Sciences, 2022)
Reactive Powder Concrete (RPC) is a combined material that will allow the concrete industry to enhance material consumption, produce economic benefits, be more durable, and be more environmentally friendly. Due to the highly dense microstructure of RPC, it performs poorly at high temperatures due to the formation of high pore pressure, which causes material breakdown. This paper demonstrates the outcomes of an investigational study of the behavior of six RPC mixes incorporating hybrid steel and plastic waste (polypropylene) fibers after being subjected to high temperatures of up to 500 ºC. Residual compressive strength, residual splitting strength, and density were performed for all the RPC mixes. The results demonstrate that the drop in the compressive strength of RPC is greater than the reduction in their corresponding splitting strength. Furthermore, within a temperature range of about 500 ºC, this mechanical strength showed a noticeable decrease. The decrement of splitting strength ranged between about 8% to 33% . Steel and polypropylene fibers also improve the residual strength of RPC samples. On the basis of these results, a mix containing mixed fibers (25 % steel and 75 % polypropylene) is recommended as appropriate for extreme temperature applications.